Improving stroke outcome: the benefits of increasing availability of technology - Richard F. Heller; Peter Langhorne; Erica James (The World Health Organization, 2000)
INTRODUCTION: A decision analysis was performed to explore the potential benefits of interventions to improve the outcome of patients admitted to hospital with a stroke, in the context of the technology available in different parts of the world. METHODS: The outcome of death or dependency was used with a six-month end-point. RESULTS: Four settings were identified that would depend on the resources available. The proportion of stroke patients who were dead or dependent at six months was 61.5% with no intervention at all. Setting 4, with the only intervention being the delayed introduction of aspirin, produced a 0.5% absolute improvement in outcome (death or dependency), and the addition of an organized stroke unit (Setting 3) produced the largest incremental improvement, of 2.7%. Extra interventions associated with non-urgent computed tomography and thus the ability to avoid anticoagulation or aspirin for those with a haemorrhagic stroke (Setting 2), and immediate computed tomography scanning to allow the use of thrombolytics in non-haemorrhagic stroke (Setting 1), produced only small incremental benefits of 0.4% in each case. DISCUSSION: To reduce the burden of illness due to stroke, efforts at primary prevention are essential and likely to have a greater impact than even the best interventions after the event. In the absence of good primary prevention, whatever is possible must be done to reduce the sequelae of stroke. This analysis provides a rational basis for beginning the development of clinical guidelines applicable to the economic setting of the patient.